STUDENTS’ ABILITY TO READ STATISTICAL DIAGRAM - Sugeng Sutiarso (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
Reading diagrams is an important ability needed by college students, particularly to writing their thesis. This ability could help students in describing and communicating the results of their research. Conversely, the inability to read diagrams causes errors in interpreting the results of the research. This descriptive qualitative study aims to describe the ability of students to read diagrams in terms of gender differences and the tendency to choose problems between bar/line diagrams, and the reasons behind the difficulties for students reading diagrams. This study involved 25 students of Mathematics Education, University of Lampung. Research data were collected using test and interview instrument. The results showed that students’ability both male and female to read diagrams was classified as moderate, the ability to read bar charts of female students was higher than that of male students but the ability to read line diagrams of male students was higher than female students, female students tend to choose bar diagrams rather than line diagrams while male students tend to choose line diagrams rather than bar diagrams, and the cause of difficulties in reading diagrams for female students were errors in understanding the meaning words while male students were errors of logical thinking in associating data with other data.